Pollyanna - Porter, Eleanor H. (Eleanor Hodgman), 1868-1920 ([Boston, Mass] : Thomson Heinle, 2007)
When orphaned, eleven-year-old Pollyanna comes to live with austere and wealthy Aunt Polly, her philosophy of gladness brings happiness to her aunt and other unhappy members of the community
Title from container
Keywords: American literature; Orphans -- Fiction; Aunts -- Fiction; Conduct of life -- Fiction; Cheerfulness -- Fiction; Interpersonal relations -- Fiction